Ecofriendly synthesis of pyrimidine derivatives: exploring their anticoccidial efficacy and cytotoxic effect on WI-38 cells - Doaa A. Elsayed; Wesam S. Shehab; Mostafa I. Abdelglil; Hend A. Haikal; Mariusz Jaremko; Ahmed F. EL-Farargy; Sahar M. Mousa; Gehan T. El-Bassyouni; Samar M. Mouneir; Marwa M. Khalifa (Journal of Saudi Chemical Society, 2025)
Abstract A number of new heterocyclic compounds based on the pyrimidine moiety were created, with potential antiparasitic characteristics. The starting material, 4-(4-cyanophenyl)-6-oxo-2-thioxohexahydropyrimidine-5-carbonitrile (1), was synthesized using two methods: a conventional approach involving thiourea, ethyl cyanoacetate, and 4-cyanobenzaldehyde refluxed in ethanol with triethylamine, and a more efficient nanoparticle-catalyzed method using TiO2 or Mn3O4. The chemicals were evaluated against coccidiosis, a parasite illness caused by Eimeria spp. Cytotoxicity tests using Wi38 human lung fibroblasts showed that compound 20 had the lowest IC50 (195.83 ± 1.56 µg/ml), indicating great potency, while compound 11 had the highest IC50 (934.03 ± 5.65 µg/ml), indicating a safer profile. Compounds 16 and 20 inhibited sporulation very completely (~ 98%) at 200 ppm, whereas compound 13 was also effective. Compounds 6, 7, and 11 exhibited moderate efficacies. These results highlight compounds 16 and 20 as strong candidates for further exploration in antiparasitic treatments, particularly for managing coccidiosis. Graphical Abstract